2021
DOI: 10.32890/jes2021.3.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Economic Growth and Human Development Index on Poverty in Indonesia

Abstract: Indonesia’s economic growth, which ranges from 5% - 6% per year, apparently has not been able to reduce the number of poor people. There has even been an increase in the total of poor people, which is currently around 37 million people. A World Bank study shows that almost 50% of Indonesia’s population is categorised as “poor” and “on the verge of poverty”. The problem of poverty deserves significant attention from all parties. Economic growth accompanied by an increase in the number of poor people is certainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
4
4
0
1
Order By: Relevance
“…Research results in Indonesia suggest that fiscal policies play an important role in improving economic growth and reducing unemployment and poverty (Hasan, 2021). Similar results found by Rindayati (2009), Mardiasmo (2009), Sumardi (2014), and Surjaningsih et al (2012) showed that an increase in government capital expenditure has a positive impact on economic growth.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Research results in Indonesia suggest that fiscal policies play an important role in improving economic growth and reducing unemployment and poverty (Hasan, 2021). Similar results found by Rindayati (2009), Mardiasmo (2009), Sumardi (2014), and Surjaningsih et al (2012) showed that an increase in government capital expenditure has a positive impact on economic growth.…”
Section: Introductionsupporting
confidence: 68%
“…25/1999 on Financial Balance between Central Government and Regional Government. The law is then revised with UU No.33/2004 (Hasan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(2021) dalam penelitiannya menunjukkan adanya dampak signifikan ke arah negatif variabel IPM pada pemberantasan kemiskinan daerah Sumatera Utara. Hasan (2021), menemukan bahwa terdapat dampak signifikan ke arah negatif variabel IPM pada tingkat kemiskinan di Indonesia.…”
Section: Pengaruh Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinanunclassified
“…All of these affect the welfare of the people at large. Strengthening the role and institutions of government is very important to support the success of investment policies (Hasan, 2021d). The attractiveness of investment can be done in various ways, including improving licensing services, increasing legal certainty, increasing market diversification and encouraging local commodities with high added value (Hong & Jeong, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%